Mutations and intron polymorphisms in voltage-gated sodium channel genes of different geographic populations of Culex pipiens pallens/Culex pipiens quinquefasciatus in China - Wenyu Li; Delong Ma; Qunzheng Mu; Xinxin Zhou; Dongdong Hua; Chunchun Zhao; Qiyong Liu; Jun Wang; Fengxia Meng (BMC, 2024)
Abstract Background Culex pipiens pallens and Culex pipiens quinquefasciatus are the dominant species of Culex mosquitoes in China and important disease vectors. Long-term use of insecticides can cause mutations in the voltage-gated sodium channel (vgsc) gene of mosquitoes, but little is known about the current status and evolutionary origins of vgsc gene in different geographic populations. Therefore, this study aimed to determine the current status of vgsc genes in Cx. p. pallens and Cx. p. quinquefasciatus in China and to investigate the evolutionary inheritance of neighboring downstream introns of the vgsc gene to determine the impact of insecticides on long-term evolution. Methods Sampling was conducted from July to September 2021 in representative habitats of 22 provincial-level administrative divisions in China. Genomic DNA was extracted from 1308 mosquitoes, the IIS6 fragment of the vgsc gene on the nerve cell membrane was amplified using polymerase chain reaction, and the sequence was used to evaluate allele frequency and knockdown resistance (kdr) frequency. MEGA 11 was used to construct neighbor-joining (NJ) tree. PopART was used to build a TCS network. Results There were 6 alleles and 6 genotypes at the L1014 locus, which included the wild-type alleles TTA/L and CTA/L and the mutant alleles TTT/F, TTC/F, TCT/S and TCA/S. The geographic populations with a kdr frequency less than 20.00% were mainly concentrated in the regions north of 38° N, and the geographic populations with a kdr frequency greater than 80.00% were concentrated in the regions south of 30° N. kdr frequency increased with decreasing latitude. And within the same latitude, the frequency of kdr in large cities is relatively high. Mutations were correlated with the number of introns. The mutant allele TCA/S has only one intron, the mutant allele TTT/F has three introns, and the wild-type allele TTA/L has 17 introns. Conclusions Cx. p. pallens and Cx. p. quinquefasciatus have developed resistance to insecticides in most regions of China. The neighboring downstream introns of the vgsc gene gradually decreased to one intron with the mutation of the vgsc gene. Mutations may originate from multiple mutation events rather than from a single origin, and populations lacking mutations may be genetically isolated. Graphical Abstract